PENERAPAN METODE PROFILE MATCHING DALAM PEMILIHAN PRODUK PELEMBAB SOMETHINC UNTUK KONDISI KULIT NORMAL TO OILY - Wilianti, Livia; Elisa, Erlin (Computer Science and Industrial Engineering, 2025)
This study addresses the core issue of consumers experiencing difficulties in selecting suitable moisturizer products for normal to oily skin, amidst the rapid growth of the skincare industry in Indonesia. The objective of this research is to calculate the gap between the ideal and actual profiles in order to identify the degree of compatibility based on predefined criteria, as well as to determine the relevant attributes involved in forming both profiles. The research employs the Profile Matching method as the primary approach to analyze the alignment between product alternatives and the ideal consumer profile. The research design includes the identification of research type, determination of population and sample, data collection procedures through online questionnaires, and data analysis methods. The findings indicate that the Profile Matching method is effective in identifying the most suitable moisturizer product from the Somethinc brand for normal to oily skin. The analysis produces a ranking of products based on the total scores calculated, assisting users in understanding product suitability, effectiveness, and usage behavior. A small or zero gap between the ideal and actual profiles signifies a high degree of compatibility, demonstrating that this method is capable of providing accurate product recommendations. The key aspects contributing to profile formation include product suitability (skin type, skin reaction, product match), usage behavior (frequency of use, awareness of skin type, intention to continue usage), and product effectiveness (variants tried, perceived improvements, and product knowledge).